Soil Organic Matter Status Under Different Social Forestry Plantations - Jha, M. N.; Gupta, M. K.; Dimri, B. M. (Indian Forester, 1999)
A study was conducted in Langha Forest Range of Mussoorie Forest Division under 15 years old plantations of Pinus roxburghii, Tectona grandis, Dalbergia sissoo, Eucalyptus, Acacia catechu along with natural Shorea robusta forest and barren land to find out the status of soil organic matter. This study was conducted before and after monsoon to investigate the changes in SOM due to change of seasons. Before monsoon it was observed that SOM content was higher under natural Shorea robusta followed by Dalbergia sissoo, Eucalyptus, Tectona grandis, Acacia catechu and Pinus roxburghii plantations and least under barren land and after monsoon it was higher under Eucalyptus only in top (0-10 cm) layer but over all higher under the soils of natural Shorea robusta followed by Eucalyptus, Dalbergia sissoo, Pinus roxburghii, Acacia catechu, Tectona grandis and least under barren land. In general SOM was observed higher in post-monsoon in comparison to pre- monsoon period.